Introducing of the methods of pollutants detecting and species used as experiment organisms in testing laboratories (ro) - Romeo T. Cristina; Doma O. Alexandru; Crina L. Mosneang (Medicamentul Veterinar)
Zebrafish are vertebrate animals often used in research for wastewaters, environment chemicals, cancer and diabetes drugs due to their speed and ease for handling and obtaining test results. Organisms capacity to detect and avoid contaminated soils reveals soils stressor potential and has an ecological relevance indepted with its direct relationship to soil biodiversity and it’s quality as a habitat for the organism. Soil pollution tests were accomplished on arthropods (Collembola), earthworms, oligochaete worms (Enchytraeidae), this being behavior modification tests, observing which species avoids contaminated soils and if response intensity depends on contamination degree. Using Daphnia sp. for testing it’s possible because of their sensibility to an amount of aquatic pollutants and also for their small sizes involving a use of small volumes of test substance and water for dilution.